ANALISIS KETEPATAN WAKTU PROSES DOCKING DAN UNDOCKING AVIOBRIDGE DI YOGYAKARTA INTERNATIONAL AIRPORT - Wiyantoro, Lukas Tri Puji; Radito, Thomas Aquinas (Sekolah Tinggi Ilmu Ekonomi SBI, 2025)
ABSTRACT This study aims to analyze the punctuality of the aviobridge docking and undocking processes at Yogyakarta International Airport (YIA) based on the existing Standard Operating Procedure (SOP), which specifies two minutes for each process. The research employed a quantitative descriptive approach using both primary and secondary data obtained from aviobridge utilization logs during the period of October to December 2024. The analysis involved calculating the average actual duration of docking and undocking processes and comparing them with the SOP standard time to determine the level of punctuality. The results indicate that the average actual duration for the docking process ranged from 75 to 102 seconds, while the undocking process ranged from 67 to 113 seconds, all of which were below the SOP limit of 120 seconds. The punctuality rate reached 95.5% in October and 100% in November and December, demonstrating high operational efficiency of the aviobridge system at YIA. Therefore, it can be concluded that the operational performance of the aviobridge at YIA is highly efficient, although it is recommended that the SOP duration be re-evaluated to better reflect the actual field conditions. Keywords : Aviobridge, Docking, Undocking, Punctuality, Yogyakarta International Airport